What’s hidden behind Lennox-Gastaut syndrome? - E. D. Belousova (Эпилепсия и пароксизмальные состояния)
A number of epileptologists often diagnose Lennox-Gastaut syndrome, while others almost never do. It is necessary to understand why this is happening, especially since Lennox-Gastaut syndrome, according to literature descriptions, is quite common. Aim. To systematize available data on Lennox-Gastaut syndrome, which will help to improve the quality of diagnosis and management of patients.Materials and methods. Qualitative scientific publications from the International Scientific Databases (ISDS), including peer-reviewed journals and monographs, were selected for the review. The plan of the review included a brief description of the syndrome; seizure types; EEG features; diagnosis criteria; treatment.Results and discussion. None of the seizure types are pathognomonic for Lennox-Gastaut  syndrome. The syndrome is considered to be confirmed if typical seizures (predominantly tonic) with typical interictal patterns without atypical EEG characteristics are reported. A diagnosis of the syndrome is considered probable if there are typical EEG patterns of waking and sleeping, but no tonic seizures are detected. The first choice of the treatment is valproate. Possible alternatives are lamotrigine and topiramate. Rufinamide and zonisamide are available as the second line of antiepileptic drugs. Rufinamide should be used when there is no effect from valproate and lamotrigine. Rufinamide also has antiabsance activity.Conclusion. “Classic” Lennox-Gasto syndrome is rare. Cases of “probable” Lennox-Gasto syndrome are much more frequent, and not all criteria of its diagnosis are observed. Taken into account the blurring of the diagnosis criteria for Lennox-Gasto syndrome and data on the efficacy of rufinamide in children with another epilepsies, it is possible to use this drug not only for Lennox-Gasto syndrome, but also for other epileptic syndromes, especially those with dropattacks, tonic seizures and atypical absences.